Some generic features of «conversations» («illustrated stories») about the trips of the 1950–60s - Morozowa, Elena I. (Journal of the Belarusian State University. Journalism, 2019)
In the article the phenomenon of «conversations» or «illustrated stories» about travels on Belarusian television of the 1950–60s – domestic travel essays, formally similar to modern blogs – was explored for the first time. It was determined that TV-trips were not entertainment, but socio-political programs, combined journalistic and philosophical principles, characterized by specific tools for embodiment of subjectivity, the creation of the illusion of movement, as well as the implementation of the method of historicism, typical and artistic images, topical diversity – the achievements that should be used in modern television production.
Keywords: «conversation»; «illustrated story»; television travel essay; psychology; virtual viewer; symbolism of illustrations; associative editing